The apology of the periphery - Kapustin, Petr (project baikal, 2023)
Not so long ago it seemed that the problem of borders remained only in philosophical, artistic and epistemological contexts. Regions had no borders. They were perceived as peripheries, regardless of their location. Regions do not want to be identified with a hinterland, that is why we have “centres” everywhere. In the hindermost of the villages, there are several “centres”: shopping, leisure, cultural, religious, etc. While thinking only in terms of centres, clusters and nodes, we tend to overlook a large part of the world that consists of peripheries, provinces, suburbs, hinterlands... It is time to rethink this trend and to look into the key concepts. Especially as today there is a good reason to recall the concept of the frontier and to newly distinguish it from the border. Rethinking, on the other hand, opens up a new, unexpected structure of the world, with which the known types of activity are hardly familiar.